Penguatan Pendidikan Karakter terhadap Sikap Peduli Lingkungan Siswa Kelas III di MI Ta’lim Mubtadi 1 - Muttaqin, Muhammad Fauzan; Maryanti, Novi Dwi (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2024)
This research focuses on strengthening character education on the environmental care attitude of third grade students at MI Ta'lim Mubtadi 1, Cipondoh. The purpose of this study is to analyze the application of strengthening character education for students' environmental care and its obstacles. This research uses a qualitative descriptive method. Data collection methods used observation, semi-structured interviews and documentation. Using source and technique triangulation to validate the data. Data analysis is done through data collection, reduction, data display and conclusions. The results showed that the implementation of strengthening character education for environmental care attitudes was integrated through learning planning, learning processes and learning assessments, as well as school programs. This activity is oriented towards habituating the character of environmental care so that it becomes a good habit that is carried out without coercion and its implementation is class-based, school culture-based and community-based. The obstacles are the lack of awareness in students to keep the environment clean and the lack of cooperation between the school and parents in providing an understanding of the importance of environmental care attitudes.